Nitrites, Nitrates, and Cardiovascular Outcomes: Are We Living “La Vie en Rose” With Pink Processed Meats? - Bernard Srour; Eloi Chazelas; Léopold K. Fezeu; Guillaume Javaux; Fabrice Pierre; Inge Huybrechts; Serge Hercberg; Mélanie Deschasaux‐Tanguy; Emmanuelle Kesse‐Guyot; Mathilde Touvier (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Nitrates and nitrites are used as food additives in processed meats. They are also commonly ingested from water and several foods. Several short‐term clinical studies suggested beneficial effects of dietary nitrates on blood pressure, while deleterious effects on oxidative damage have been suggested in some experimental studies. However, there is a lack of evidence from longitudinal epidemiological studies linking foods and water‐originated and additives‐originated nitrites and nitrates, separately, to hypertension and cardiovascular diseases risk. We aimed to study these associations in a large population‐based cohort. Methods and Results Overall, 106 288 adults from the French NutriNet‐Santé cohort (2009–2022) were included. Associations between nitrites and nitrates intakes and hypertension and cardiovascular disease risks were assessed using multi‐adjusted Cox proportional hazard models. During follow‐up, 3810 incident cases of hypertension and 2075 cases of cardiovascular diseases were ascertained. Participants with higher intakes of additives‐originated nitrites (sodium nitrite in particular [European code e250]) had a higher hypertension risk compared with nonconsumers (hazard ratio, 1.19 [95% CI, 1.08–1.32], P=0.001, and 1.19 [95% CI, 1.08–1.32], P=0.002), respectively. No association was detected between foods and water‐originated nitrites, or nitrates with hypertension risk (all P values >0.3). We found no association between nitrites or nitrates and risks of cardiovascular diseases (all P values >0.2). Conclusions These results do not support a protective role of nitrites or nitrates in cardiovascular health. Instead, they suggest a positive association between nitrites from food additives and hypertension risk, which needs confirmation in other large‐scale studies. These findings provide new evidence in the context of current discussions about updating regulations on the use of nitrites as food additives.